Skin-moistening and face-repairing BB cream and preparation method thereof
By using the secondary spherical titanium dioxide powder formed by the condensation of primary rod-shaped crystal particles and the elastomer obtained by cross-linking of hyaluronic acid, the existing BB cream products have been solved, and the high soft focus index and the extension of makeup holding time has been achieved.
Patent Information
- Application Number
- CN202510102550.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
AI Technical Summary
Existing BB cream products are prone to floating powder and mud rubbing after use, resulting in heavy and rough makeup, and it is difficult to achieve high soft focus index and makeup holding effect.
Using secondary spherical titanium dioxide powder formed by the agglomeration of primary rod-shaped crystal particles, combined with elastomers obtained by cross-linking with hyaluronic acid or its salts, the transmittance, scattering and makeup holding time of BB cream is improved by optimizing the formulation and preparation method.
It achieves the good soft focus effect of BB cream and the extension of makeup holding time, giving the product a more natural concealer effect and a smooth touch.
Smart Images

Figure CN119818378A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, and in particular to a skin-moisturizing and face-repairing BB cream and a preparation method thereof. Background Art
[0002] BB cream is a cosmetic that combines skin care, concealer, sunscreen, and pore refinement, and is committed to creating a basic nude makeup effect. However, the BB cream products currently on the market have the phenomenon of floating powder and mud after use, resulting in a heavy and rough makeup. From the perspective of optical or visual effects, in order to obtain a more natural concealer effect, that is, a high soft focus index, after the cosmetics are applied to the surface of human skin, they need to show a high and uniform transmittance, extremely low absorption rate of visible light, and the light reflected by the skin after transmission should also be uniform; low or extremely low reflectivity, especially specular reflectivity; extremely high scattering rate and uniform reflection effect caused by scattering. In order to obtain the ideal soft focus effect, the formula is usually improved in the following ways: (1) Adding inorganic powders with high refractive index, such as titanium dioxide, zinc oxide, silicon dioxide, etc., but these materials have insufficient transparency and poor scattering properties, making the actual soft focus effect unsatisfactory; (2) Adding fillers to fill skin depressions, smooth pores and fine lines to improve skin texture, but these materials will cause severe oil secretion, thereby reducing the makeup's ability to last.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The invention provides a skin-moisturizing and face-reshaping BB cream and a preparation method thereof, aiming to provide a BB cream with good soft-focus effect and skin-moisturizing effect.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a skin-soothing and face-repairing BB cream, which comprises the following components calculated by mass percentage:
[0007] Titanium dioxide 6% to 17%, iron oxide color powder 0 to 3%, elastomer 2 to 6%, silicon powder 2% to 3%, emulsifier 2% to 7%, oil 10% to 20%, film former 0.2% to 3%, thickener 0.2% to 3%, moisturizer 8% to 20%, pH adjuster 0% to 0.2%, preservative 0.5% to 4%, antioxidant 0 to 1%, disodium EDTA 0.05% to 0.1%, balance water;
[0008] The titanium dioxide is a secondary particle formed by the aggregation of primary particles. The primary particles are rod-shaped crystals with an average major axis length of 60 to 160 nm and an aspect ratio of 5 to 8. The secondary particles are spherical particles with an average particle diameter of 1 to 3 μm.
[0009] In some embodiments, the rutile fraction of titanium dioxide is greater than 95%.
[0010] In some embodiments, the average major axis length of the primary particles of titanium dioxide is 65 to 127 nm;
[0011] In some embodiments, the primary particles of titanium dioxide have an aspect ratio of 5.4 to 7.1.
[0012] In some embodiments, the preparation method of titanium dioxide comprises the following steps: (1) dissolving TiCl4 in deionized water, performing a hydrothermal reaction, and obtaining a wet titanium dioxide powder after solid-liquid separation and washing; (2) redispersing the wet titanium dioxide powder in ammonia water, sealing and standing for aging, and finally homogenizing to obtain a suspension; (3) spray drying the suspension to obtain granulated titanium dioxide; (4) placing the granulated titanium dioxide in a suspension furnace for calcination to obtain titanium dioxide.
[0013] In some embodiments, the hydrothermal reaction temperature is 110-130° C., and the reaction time is 1.5-3 h.
[0014] In some embodiments, the sealed static aging time is 48 to 96 hours.
[0015] In some embodiments, the solid content of the suspension is 50% to 70%.
[0016] In some embodiments, the calcination temperature is 300-400° C., and the calcination time is 2-4 hours.
[0017] In some embodiments, the elastomer is obtained by cross-linking hyaluronic acid or a salt thereof.
[0018] In some embodiments, the elastomer is obtained by cross-linking hyaluronic acid or a salt thereof via an epoxy compound.
[0019] In some embodiments, the epoxy compound includes an A component and a B component; the A component is epoxidized soybean oil; and the B component is at least one selected from glycidyl ether, ethylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether.
[0020] In some embodiments, the preparation method of the elastomer is as follows: dissolving hyaluronic acid or its salt in alkaline solution, and then successively adding component A of the epoxy compound and component B of the epoxy compound to carry out stirring reaction to obtain a gel; granulating the gel and placing it in a fluidized bed for drying to obtain an elastomer.
[0021] In some embodiments, the average particle size of the elastomer is 30 to 50 μm.
[0022] In some embodiments, the alkali solution is an aqueous sodium hydroxide solution with a pH of 11-13.
[0023] In some embodiments, the temperature of the stirred reaction is 35-60°C.
[0024] In some embodiments, the iron oxide toner is at least one of yellow iron oxide, red iron oxide, and black iron oxide.
[0025] In some embodiments, the emulsifier is selected from at least one of polyglyceryl-10 decooleate, polyglyceryl-10 caprylic decanoate, polyglyceryl-10 stearate, polyglyceryl-6 distearate, polyglyceryl-3 stearate, PEG-10 dimethicone, PEG-15 dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone, and cetyl PEG / PPG-10 / 1 dimethicone.
[0026] In some embodiments, the oil is selected from at least one of isododecane, isohexadecane, isononyl isononanoate, dicaprylyl carbonate, propylheptyl caprylate, caprylic / capric triglyceride, dibutyl adipate, cyclopentasiloxane, C20-24 olefin, isopropyl myristate, isopropyl palmitate, behenyl alcohol, propylheptyl caprylate, coconut oil alcohol-caprylic / capric acid ester and silicone oil.
[0027] In some embodiments, the film former is selected from at least one of VP / VA copolymer, acrylic acid / tert-butyl acrylamide copolymer, and polyvinylpyrrolidone (PVP).
[0028] In some embodiments, the thickener is selected from at least one of agarose, xanthan gum, carrageenan, cellulose, hyaluronic acid or a salt thereof, carbomer, and magnesium aluminum silicate.
[0029] In some embodiments, the humectant is at least one of betaine, trehalose, glycerin, polyglycerin, propylene glycol, and butylene glycol.
[0030] In some embodiments, the pH adjuster is selected from at least one of citric acid, sodium hydroxide, and triethanolamine.
[0031] In some embodiments, the antioxidant is selected from at least one of tocopherol acetate, lecithin, ascorbic acid, astaxanthin, lycopene, lipoic acid, ubiquinone, and tea polyphenols.
[0032] In some embodiments, the preservative is selected from at least one of phenoxyethanol, parabens, benzoates, and acetylparaben.
[0033] In a second aspect, the present invention provides a method for preparing the skin-soothing and face-repairing BB cream in any of the above embodiments, comprising the following steps:
[0034] (1) Mix the moisturizer, disodium EDTA, and deionized water in a pot, heat to 75-80° C., stir until completely dissolved, keep warm for 10-30 minutes, and remove from the pot to obtain a water phase;
[0035] (2) Mix the emulsifier, film-forming agent, antioxidant and preservative in a pot, heat to 80-100° C., stir until completely dissolved, keep warm for 10 minutes and remove from the pot to obtain an oil phase;
[0036] (3) Mix titanium dioxide, iron oxide colorant, silica, elastomer and grease, grind until there are no particles, and then set aside to obtain powder;
[0037] Add the powder to the oil phase, transfer to an emulsifier after homogenization, heat to 60-80°C and keep warm for 10 minutes, then add the water phase, keep warm and homogenize, then add the thickener and pH adjuster, continue stirring until completely dissolved, cool and defoam to obtain a moisturizing and repairing BB cream.
[0038] The present invention has the following beneficial effects:
[0039] The present invention provides a skin-soothing and face-repairing BB cream, wherein spherical titanium dioxide powder obtained by agglomerating primary particles of rutile rod-shaped crystal particles is added to the BB cream, and the powder has both high and uniform transmittance and high scattering rate, thereby giving the BB cream a good soft-focus effect; further, an elastomer with a moisturizing function is added to the skin-soothing and face-repairing BB cream, and the elastomer can smooth wrinkles and provide a smooth touch and appearance, thereby improving the soft-focus effect and increasing the makeup-lasting time. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 SEM images of titanium dioxide T1 sample at different magnifications.
[0041] Figure 2 This is the XRD pattern of titanium dioxide T1 sample.
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0044] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0045] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0046] In the embodiment of the present application, the term "or / and" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A or / and B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0047] In addition, the character “ / ” in this article generally indicates that the previous and next associated objects are in an “or” relationship.
[0048] In the embodiments of the present application, "multiple" means more than two (including two). Similarly, "multiple groups" means more than two groups (including two groups), and "multi-layer" means more than two layers (including two layers), unless otherwise clearly specified and limited.
[0049] In the embodiments of the present application, "at least one" means one or more than one.
[0050] In the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed in a specific orientation, etc., and cannot be understood as limiting the embodiments of the present application. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application according to specific circumstances.
[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0052] Titanium dioxide
[0053] The titanium dioxide provided by the present invention is a secondary particle formed by agglomeration of primary particles, the primary particles are rod-shaped crystals with a major axis length of 20 to 160 nm and an aspect ratio of 5 to 8, the secondary particles are spherical particles with an average particle size of 1 to 3 μm, and the rutile rate of the titanium dioxide is more than 95%. Specifically, the specific embodiment of the present invention provides titanium dioxide having a structure shown in Table 1 below.
[0054] Table 1
[0055]
[0056] Commercially available nano-titanium dioxide was purchased from Shijiazhuang Jinghuang Technology Co., Ltd.
[0057] The preparation method of T1 is as follows: (1) slowly add 30 mL of TiCl4 to 100 mL of deionized water at a temperature of 4 to 10°C, keep warm and stir for 2 hours after the addition is completed, transfer to a reactor, react in an oven at 120°C for 2 hours, and after the reaction is completed, centrifuge the resulting precipitate and wash it with deionized water until it is neutral to obtain a wet titanium dioxide powder; (2) redisperse the wet titanium dioxide powder in 30 wt% ammonia water, seal it and let it stand for aging for 3 days, and then homogenize it to obtain a suspension; (3) spray dry the suspension to obtain granulated titanium dioxide with an average particle size of 3.2 μm; (4) place the granulated titanium dioxide in a suspension furnace for calcination to obtain titanium dioxide. The solid content of the suspension is 70%; the calcination temperature is 400°C, and the time is 2 hours.
[0058] The preparation method of T2 is as follows: (1) slowly add 20 mL of TiCl4 to 100 mL of deionized water at a temperature of 4 to 10°C, keep warm and stir for 2 hours after the addition is completed, transfer to a reactor, react in an oven at 110°C for 3 hours, and after the reaction is completed, centrifuge the resulting precipitate and wash it with deionized water until it is neutral to obtain a wet titanium dioxide powder; (2) redisperse the wet titanium dioxide powder in 30 wt% ammonia water, seal it and let it stand for 2 days, and then homogenize it to obtain a suspension; (3) spray dry the suspension to obtain granulated titanium dioxide with an average particle size of 1.8 μm; (4) place the granulated titanium dioxide in a suspension furnace for calcination to obtain titanium dioxide. The solid content of the suspension is 60%; the calcination temperature is 300°C, and the time is 4 hours.
[0059] The preparation method of T3 is as follows: (1) slowly add 20 mL of TiCl4 to 100 mL of deionized water at a temperature of 4 to 10°C, keep warm and stir for 2 hours after the addition is completed, transfer to a reactor, react in an oven at 130°C for 1.5 hours, and after the reaction is completed, centrifuge the resulting precipitate and wash it with deionized water until it is neutral to obtain a wet titanium dioxide powder; (2) redisperse the wet titanium dioxide powder in 30 wt% ammonia water, seal it and let it stand for 4 days, and then homogenize it to obtain a suspension; (3) spray dry the suspension to obtain granulated titanium dioxide with an average particle size of 2.4 μm; (4) place the granulated titanium dioxide in a suspension furnace for calcination to obtain titanium dioxide. The solid content of the suspension is 50%; the calcination temperature is 400°C, and the time is 3 hours.
[0060] Sample T0 is obtained by drying the wet titanium dioxide powder obtained in step (1) of preparing sample T1 in a 100° C. forced air oven for 12 hours.
[0061] Sample T0 is obtained by drying the wet titanium dioxide powder obtained in step (1) of preparing sample T1 in a 100° C. forced air oven for 12 hours.
[0062] Sample T00 was obtained by calcining sample T00 in a suspension furnace at 400°C for 2 hours.
[0063] The major axis length, aspect ratio, and secondary particle size of titanium dioxide are obtained by SEM image analysis, and the rutile rate is obtained by analyzing the XRD spectrum. The aspect ratio refers to the ratio of the major axis length to the minor axis diameter of the primary particle, and the rutile rate refers to the ratio of the rutile phase content to the total content of the rutile phase and anatase phase, which is obtained by analysis in accordance with GB / T30793-2014 "Determination of the ratio of anatase to rutile in titanium dioxide pigments by X-ray diffraction method".
[0064] Figure 1 The SEM images of sample T1 at different magnifications show that the prepared titanium dioxide is secondary particles formed by the agglomeration of primary particles.
[0065] Figure 2 This is the X-ray diffraction (XRD) diagram of sample T2. It can be seen from the diffraction pattern that the diffraction peak intensities at 2θ of 27.5° and 54.16° are both high, and the peaks are narrow and sharp, indicating that rutile phase titanium dioxide with high crystallinity is generated on the surface. This result is consistent with the standard spectrum of rutile titanium dioxide (JCPDS21-1276), and the rutile rate is >95%.
[0066] Test Example 1 Transmittance and Haze Measurement
[0067] The soft focus effect of the sample was evaluated by transmittance and haze. Specifically, the samples (T1-T3, T0, T00, commercially available nano titanium dioxide) were dispersed with glycerin to obtain a dispersion with a mass percentage of 20% to obtain a test sample. 0.20±0.01g of the test sample was evenly slid at a constant speed with an applicator to form a 3×3cm film on a transparent cardboard. The film was allowed to stand for 5 minutes and the transmittance and haze were measured with a haze meter. Each test sample was measured 3 times in parallel to take the average value. The results are listed in Table 2.
[0068] Table 2
[0069]
[0070]
[0071] Transmittance refers to the ratio of transmitted light flux to emitted light flux, and haze refers to the ratio of scattered light flux that deviates from the direction of incident light (usually greater than 2.5 degrees) to the total transmitted light flux. From the data in the table, it can be seen that samples T1 to T3 provided by the present invention have both good light transmittance and haze, indicating a good soft focus effect. In this way, light can reach the skin and illuminate the skin color, while at the same time, it has scattered transmission of light, and less light reaches the blemishes, which has a weakening effect on skin blemishes. Samples T0, T00 and commercially available nano titanium dioxide do not have secondary particle structures, and the degree of light scattering is low, so the haze is small.
[0072]
Elastomer
[0073] An elastomer is added to the moisturizing and repairing BB cream provided by the present invention. In some embodiments, the elastomer is a common commercially available silicone elastomer, polyurethane elastomer, etc.; in some embodiments, the elastomer is obtained by cross-linking hyaluronic acid or its salt; in some embodiments, the elastomer is obtained by cross-linking hyaluronic acid or its salt with an epoxy compound. The elastomer has the effect of smoothing fine lines, filling pores, and making the skin present a smooth touch and appearance, and has a significant effect on improving the soft focus effect. Compared with ordinary commercially available silicone elastomers and polyurethane elastomers, the elastomer obtained by cross-linking hyaluronic acid or its salt has higher biocompatibility with the skin, has a moisturizing effect, can reduce the secretion of sebum from the skin, avoids the phenomenon of rubbing mud and floating powder, and thus prolongs the makeup holding time. Exemplarily, a specific embodiment of the present invention provides an elastomer as shown in Table 3 below.
[0074] Table 3
[0075]
[0076]
[0077] The particle size of the elastomer is obtained by testing in accordance with GB / T 29022-2021 "Particle Size Analysis Dynamic Light Scattering Method (DLS)".
[0078] Test Example 2 Moisture Retention
[0079] The elastomer sample (E0-E4, hyaluronic acid) was dispersed with glycerol (20wt%) and water (75wt%) to obtain a 5% dispersion to obtain a test sample. 2 The test sample was applied to the marked area of 4×4cm on the inner side of the subject's arm, and gently massaged until the sample was absorbed, and then left to stand for a certain period of time (t=30min, 1h, 3h, 6h) in a constant temperature of 20°C and a constant humidity of 50%. Then the moisture value was measured with the moisture probe of the MPA580 skin tester (CK Company, Germany) and the skin moisture increase rate was calculated = (moisture value at t-moisture value before coating) / moisture value before coating. The test was averaged three times to obtain the value. The blank control group formula, calculated by mass percentage, includes the following components: 20wt% glycerol and 85% water. The subjects were 20 to 45 years old, a total of 20 people, 10 men and 10 women. The results are listed in Table 4.
[0080] Table 4: Skin moisture increase rate, unit %
[0081] Samples to be tested 30min 1h 3h 6h E0 12.4 5.4 0.7 0.4 E1 35.7 33.6 30.5 28.4 E2 30.3 28.4 27.2 26.3 E3 28.4 25.6 20.2 18.4 E4 35.5 32.3 28.2 25.7 Hyaluronic acid 22.1 24.4 18.3 5.6 Blank control group 13.3 4.5 -0.8 -0.4
[0082] As can be seen from the table, the elastomer samples E1 to E4 prepared by the method provided by the present invention have a long-lasting retention effect and can still provide moisturizing effect to the skin after 6 hours of use. Compared with E1, E4 has a faster decrease in skin moisture value over time due to the absence of epoxy soybean oil, indicating that the epoxy soybean oil fragments released during the process of skin degradation of the elastomer are beneficial to inhibit moisture volatilization and improve the moisturizing effect.
[0083] Test Example 3 Evaluation of Wrinkle Filling Efficacy
[0084] The elastomer sample E1 was dispersed with glycerol (20wt%) and water (75wt%) to obtain a 5% dispersion to obtain a test sample. The blank control group formula, calculated by mass percentage, included the following components: 20wt% glycerol, 85% water, 3.0±0.1mg / cm 2 The test sample and the blank control group were applied to the left and right corners of the subjects' eyes, and gently massaged until the sample was absorbed. Then, after standing for a certain period of time (t = 30min, 1h, 3h, 6h) in a constant temperature 20°C and constant humidity 50% environment, the average wrinkle depth was measured using a 3D skin rapid imaging system (German PRIMOS Company), and the average wrinkle depth increase value was calculated = (average wrinkle depth at t - average wrinkle depth before application) / average wrinkle depth before application. The subjects were 20 people aged 20 to 45, 10 men and 10 women. The results are listed in Table 5.
[0085] Table 5
[0086] Samples to be tested 30min 1h 3h 6h E1 --2.74 -2.72 -1.85 -1.51 Blank control group -0.24 -0.05 0.02 -0.04
[0087] It can be seen from the data in the table that the elastomer E1 provided by the present invention has the effect of smoothing and filling wrinkles.
[0088] A moisturizing and repairing BB cream having the formula shown in Table 6 below is provided.
[0089] Table 6: Formulation, unit %
[0090]
[0091]
[0092]
[0093] The preparation methods of the above-mentioned Examples 1 to 9 and Comparative Example 1 are as follows:
[0094] (1) Mix the moisturizer, disodium EDTA, and deionized water in a pot, heat to 75-80° C., stir until completely dissolved, keep warm for 20 minutes, and remove from the pot to obtain a water phase;
[0095] (2) Mix the emulsifier, film-forming agent, antioxidant and preservative in a pot, heat to 85-90° C., stir until completely dissolved, keep warm for 10 minutes and remove from the pot to obtain an oil phase;
[0096] (3) Mix titanium dioxide, iron oxide colorant, silica, elastomer and grease, grind until there are no particles, and then set aside to obtain powder;
[0097] (4) Add the powder to the oil phase, homogenize and transfer to an emulsifier, heat to 70-80°C and keep warm for 10 minutes, then add the water phase, keep warm and homogenize, then add the thickener and pH adjuster, continue stirring until completely dissolved, cool and defoam to obtain a moisturizing BB cream.
[0098] Test Example 4: Haze Test
[0099] According to the method of Test Example 3, the samples (Examples 1 to 9, Comparative Example 1) were evenly slid at a uniform speed using a coater to form a film with a thickness of 2 μm on transparent cardboard. The film was allowed to stand for 5 minutes and the transmittance and haze were measured using a haze meter. Each test sample was measured 3 times in parallel to take the average value. The results are listed in Table 6.
[0100] Test Example 5: Makeup lasting effect test
[0101] The colorimeter was used to measure the LAB values of different makeup holding times, and then △E was calculated to evaluate the makeup holding effect. Specifically, 0.10±0.01g of the sample was evenly applied to the forehead with a fingertip, and the application area was 3cm×3cm. The values of L, a, and b were measured immediately after the sample was applied and 4 hours after application, and △E was calculated as (△L) 2 +(△a) 2 +(△b) 2 The subjects were 20 people aged 20 to 45, 10 of them were male and 10 of them were female. Each subject could test two samples at the same time until all samples were tested. The results are listed in Table 6.
[0102] Table 6
[0103] Test samples Haze, % △E Example 1 94.5 0.44 Example 2 96.8 0.52 Example 3 97.2 0.57 Example 4 98.4 0.50 Example 5 96.4 0.48 Example 6 94.3 0.46 Example 7 98.2 0.58 Example 8 98.7 0.65 Example 9 98.5 0.82 Comparative Example 1 82.4 1.44
[0104] Haze reflects the light scattering ability of the moisturizing and repairing BB cream, that is, it reflects the soft focus effect of the BB cream. From the data in the table, it can be seen that the embodiment has a better soft focus effect than the comparative example. Comparison between Example 4 and Example 1 shows that the higher the amount of titanium dioxide added, the better the soft focus effect; comparison between Examples 4, 5, and 6 and Comparative Example 1 shows that the difference between the four is that different titanium dioxide samples are used, indicating that the titanium dioxide sample has a significant effect on the soft focus effect. The soft focus effect of titanium dioxide is ranked as follows: T1>T2>T3>T00, indicating that the longer the major axis length of the primary particles of titanium dioxide and the larger the average particle size of the secondary particles, the better the soft focus effect, and the secondary particles have a better soft focus effect than the primary particles.
[0105] △E reflects the makeup-lasting effect of the moisturizing and repairing BB cream. The larger the △E, the greater the difference between the color immediately after application and the color 4 hours after application, indicating that the makeup-lasting property is worse. As can be seen from the table, the embodiment has a better makeup-lasting effect than the comparative example, indicating that the secondary particles of titanium dioxide have better adhesion and antioxidant capacity on the skin than the primary particles. In addition, by comparing Examples 4, 7 to 9, it can be seen that the difference between the four is that different elastomer samples are used, and the elastomer samples have a significant effect on the makeup-lasting effect. The makeup-lasting effect of the elastomer is ranked as follows: E1>E3>E4>E0, indicating that the elastomer prepared by hyaluronic acid has a moisturizing function, so it is beneficial to improve the makeup-lasting effect compared with the silicone elastomer. In addition, the addition of epoxy soybean oil improves the moisturizing function, so Examples 1 and 7 have a higher makeup-lasting effect than Example 8, but the amount of epoxy soybean oil added should not be too much. Too much will lead to a large oil content and excessive oil production, which is not conducive to makeup-lasting.
[0106] In summary, the present invention provides a skin-smoothing and face-reshaping BB cream, which has both good soft-focus effect and moisturizing properties, and is therefore beneficial for improving the smoothness of makeup and prolonging the makeup-lasting time.
[0107] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A skin-moisturizing and face-reshaping BB cream, characterized in that: Calculated by mass percentage, it includes the following components: 6% to 17% titanium dioxide, 0% to 3% iron oxide color powder, 2% to 6% elastomer, 2% to 3% silicon powder, 2% to 7% emulsifier, 10% to 20% oil, 0.2% to 3% film former, 0.2% to 3% thickener, 8% to 20% moisturizer, 0% to 0.2% pH adjuster, 0.5% to 4% preservative, 0% to 1% antioxidant, 0.05% to 0.1% disodium EDTA, and the balance is water; The titanium dioxide is a secondary particle formed by the aggregation of primary particles. The primary particles are rod-shaped crystals with an average major axis length of 60 to 160 nm and an aspect ratio of 5 to 8. The secondary particles are spherical particles with an average particle diameter of 1 to 3 μm.
2. The skin-soothing and face-reshaping BB cream according to claim 1, characterized in that: The rutile rate of the titanium dioxide is above 95%; and / or, the average major axis length of the primary particles of titanium dioxide is 65 to 127 nm; And / or, the aspect ratio of the primary particles of titanium dioxide is 5.4 to 7.
1.
3. The skin-soothing and face-reshaping BB cream according to claim 1 or 2, characterized in that: The preparation method of titanium dioxide comprises the following steps: (1) dissolving TiCl4 in deionized water, performing a hydrothermal reaction, and obtaining a titanium dioxide powder wet material after solid-liquid separation and washing; (2) redispersing the titanium dioxide powder wet material in ammonia water, sealing and standing for aging, and finally homogenizing to obtain a suspension; (3) spray-drying the suspension to obtain granulated titanium dioxide; and (4) calcining the granulated titanium dioxide in a suspension furnace to obtain titanium dioxide.
4. The skin-soothing and face-reshaping BB cream according to claim 3, characterized in that: The hydrothermal reaction temperature is 110-130°C and the reaction time is 1.5-3h; And / or, the sealing static aging time is 48 to 96 hours; and / or, the solid content of the suspension is 50% to 70%; And / or, the calcination temperature is 300-400° C. and the calcination time is 2-4 hours.
5. The skin-soothing and face-reshaping BB cream according to claim 1 or 2, characterized in that: The elastomer is obtained by cross-linking hyaluronic acid or its salt via an epoxy compound; And / or, the average particle size of the elastomer is 30 to 50 μm.
6. The skin-soothing and face-reshaping BB cream according to claim 5, characterized in that: The epoxy compound comprises component A and component B; the component A is epoxy soybean oil; and the component B is at least one selected from glycidyl ether, ethylene glycol diglycidyl ether and 1,4-butanediol diglycidyl ether.
7. The skin-soothing and face-reshaping BB cream according to claim 6, characterized in that: The preparation method of the elastomer is as follows: dissolving hyaluronic acid or its salt in alkaline solution, and then stirring the component A and the component B in sequence to obtain a gel; and granulating the gel and drying it in a fluidized bed to obtain an elastomer.
8. The skin-soothing and face-reshaping BB cream according to claim 7, characterized in that: The alkali solution is a sodium hydroxide aqueous solution with a pH of 11 to 13; And / or, the stirring reaction temperature is 35-60°C.
9. The skin-soothing and face-reshaping BB cream according to claim 1, characterized in that: The iron oxide toner is at least one of yellow iron oxide, red iron oxide and black iron oxide; and / or, the emulsifier is at least one selected from polyglyceryl-10 decooleate, polyglyceryl-10 caprylic decanoate, polyglyceryl-10 stearate, polyglyceryl-6 distearate, polyglyceryl-3 stearate, PEG-10 dimethicone, PEG-15 dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone and cetyl PEG / PPG-10 / 1 dimethicone; And / or, the oil is selected from at least one of isododecane, isohexadecane, isononyl isononanoate, dicaprylyl carbonate, propylheptyl octanoate, caprylic / capric triglyceride, dibutyl adipate, cyclopentasiloxane, C20-24 olefin, isopropyl myristate, isopropyl palmitate, behenyl alcohol, propylheptyl octanoate, coconut oil alcohol-caprylic / capric ester and silicone oil; And / or, the film-forming agent is selected from at least one of VP / VA copolymer, acrylic acid (ester) / tert-butyl acrylamide copolymer and polyvinyl pyrrolidone (PVP); and / or, the thickener is selected from at least one of agarose, xanthan gum, carrageenan, cellulose, hyaluronic acid or its salt, carbomer and magnesium aluminum silicate; and / or, at least one of the moisturizing agents betaine, trehalose, glycerol, polyglycerol, propylene glycol and butylene glycol; And / or, the pH regulator is selected from at least one of citric acid, sodium hydroxide and triethanolamine; And / or, the antioxidant is selected from at least one of tocopherol acetate, lecithin, ascorbic acid, astaxanthin, lycopene, lipoic acid, ubiquinone and tea polyphenols; And / or, the preservative is selected from at least one of phenoxyethanol, paraben, benzoate and acetylparaben.
10. The method for preparing the skin-soothing and face-reshaping BB cream according to claim 1, characterized in that: The following steps are involved: (1) Mix the moisturizer, disodium EDTA, and deionized water in a pot, heat to 75-80° C., stir until completely dissolved, keep warm for 10-30 minutes, and remove from the pot to obtain a water phase; (2) Mix the emulsifier, film-forming agent, antioxidant and preservative in a pot, heat to 80-100° C., stir until completely dissolved, keep warm for 10 minutes and remove from the pot to obtain an oil phase; (3) Mix titanium dioxide, iron oxide colorant, silica, elastomer and grease, grind until there are no particles, and then set aside to obtain powder; (4) Add the powder to the oil phase, homogenize and transfer to an emulsifier, heat to 60-80°C and keep warm for 10 minutes, then add the water phase, keep warm and homogenize, then add the thickener and pH adjuster, continue stirring until completely dissolved, cool and defoam to obtain a moisturizing BB cream.